A SWOT ANALYSIS OF THE SOCIALIZATION STRATEGY FOR NEW STUDENT RECRUITMENT - Risma Oktariani; Saipul Annur; Lia Efriliyanti (EDUCATIONE, 2026)
This study examines the socialization strategy used in new student recruitment at MTs Negeri 1 Palembang and explores how the strategy can be interpreted through a SWOT framework. A qualitative descriptive design was employed to capture how recruitment-related socialization is planned, implemented, and evaluated in the institutional setting. Data were collected through non-participant observation, semi-structured interviews, and documentation involving the principal, the vice principal for student affairs, the PPDB committee chair, teachers involved in promotion, parents, and prospective students. The data were analyzed through data reduction, data display, and conclusion drawing, while triangulation was used to enhance the trustworthiness of the findings. The results indicate that the madrasah implements socialization through a combination of digital and face-to-face channels, including social media, brochures, school visits, and direct communication with parents and feeder schools. Its key strengths include institutional reputation, qualified human resources, and adequate facilities, whereas its main weaknesses lie in the limited variety of promotional content and the suboptimal use of digital communication. Externally, the institution benefits from growing public interest in Islamic education and wider access to communication technology, but it also faces strong competition from other schools and changing parental expectations. The study concludes that SWOT analysis is useful not only for identifying strategic factors but also for formulating more adaptive, focused, and sustainable socialization strategies for student recruitment.